Upaya Perlindungan Hukum terhadap Pelaku Anak di Bawah Umur yang Terlibat sebagai Kurir Narkotika - M. Abi Febriansyah; Zainudin Hasan (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This research is focused on understanding the factors that cause children to be involved in drug abuse. It is important to realize that children play an important role in society and as the future leaders of the nation. The use of narcotics by children, especially their involvement as couriers, is a growing concern in different segments of society. Involvement in this illegal drug trade is a serious problem, and the use of children as couriers is part of a larger criminal conspiracy. When children are used as narcotics couriers, this becomes a very concerning problem because they will face legal consequences and are considered to have committed narcotics crimes. Whether as perpetrators or victims, children involved in narcotics-related activities will be punished in accordance with the law. This study aims to identify the causative factors that cause children to be used as narcotics couriers. . Children are easily influenced by environmental, family, and economic factors because they are still developing mentally and thinking. They are often promised money or valuables by irresponsible parties. It is essential to educate children to make good choices and avoid committing crimes. Parents play a key role in supervising their children's socializing, as not paying attention to this can cause children to misassociate and potentially commit criminal acts.